An uncommon hero M.K. Rajakumar in politics and and medicine - Tan, Pek Leng (Strategic Information and Research Development Centre (SIRD), 2011)
Many witness momentous events in their lives, but few participate, much less leave their mark. Dr M. K Rajakumar, on the contrary, left an indelible mark at every phase of his eventful life.